Why does the moon change shape? - Stewart, Melissa (New York : Marshall Cavendish Benchmark, 2009)
Photographs and simple text explain why the moon appears to change its shape every night.
The mysterious moon -- Our place in space -- The moon in motion -- Let their be light -- Why does the moon change shape?
Includes bibliographical references (p. 31) and index.
4.0
3-6
Keywords: Moon -- Juvenile literature; Moon -- Phases -- Juvenile literature; Moon; Moon -- Phases; Moon